Quizizz as a Digital Formative Assessment and its Contribution to the Fiqh Learning Outcomes of Madrasah Students - Halimah Sari; Risnawati Risnawati (PT. Pusmedia Group Indonesia, 2026)
Digital learning media are increasingly needed in madrasah classrooms because students are already familiar with interactive online environments while teachers are required to provide learning experiences that are measurable, engaging, and responsive. This study aims to examine the effect of Quizizz learning media on students' Fiqh learning outcomes at MTsS Madinatun Najah Rengat. The study was conducted during the odd semester of the 2025/2026 academic year and used a quantitative correlational design with simple linear regression. The sample consisted of 30 students who had participated in Fiqh learning supported by Quizizz. Data were collected through a Quizizz learning media questionnaire and documentation of students' Fiqh learning outcomes. The data were analyzed using validity and reliability testing, Shapiro-Wilk normality testing, linearity testing, simple linear regression, the t test, the F test, and coefficient of determination with SPSS 24. The normality test showed that the Quizizz media variable and learning outcome variable were normally distributed, with significance values of .370 and .055. The linearity test showed that the relationship between variables was linear, with a deviation from linearity value of .096. The regression results showed a strong positive relationship between Quizizz and learning outcomes, with R = .786 and R square = .617. The regression model was significant, F = 45.150, p < .001, and the Quizizz media coefficient was positive and significant, B = 1.162, t = 6.719, p < .001. These findings indicate that Quizizz contributes 61.7% to the variation in students' Fiqh learning outcomes. Quizizz can therefore be used as an effective digital learning and assessment medium in madrasah when it is aligned with learning objectives, followed by feedback, and supported by teacher facilitation.